Cover Feature: An Advanced 'clickECM' That Can be Modified by the Inverse‐Electron‐Demand Diels‐Alder Reaction (ChemBioChem 1/2022). (12th October 2021) - Nellinger, Svenja; Rapp, Mareike A.; Southan, Alexander; Wittmann, Valentin; Kluger, Petra J.
Abstract : The extracellular matrix (ECM) is a promising biomaterial for numerous applications. Using cells from human donors and synthetic carbohydrate derivatives, a functionalized ECM modified with dienophiles, such as cyclopropenes, was produced by metabolic glycoengineering. The cover feature highlights the application of the inverse‐electron‐demand Diels‐Alder reaction to "click" variable groups R to the ECM in a cell‐friendly manner. In this way, the ECM can be equipped with new biological or chemical functions, which opens a wide range of future applications. (Image created with BioRender.com.) More information can be found in the Full Paper by V. Wittmann, P. J. Kluger et al.